Dopamine alleviates bisphenol A-induced phytotoxicity by enhancing antioxidant and detoxification potential in cucumber. (April 2020) - Ahammed, Golam Jalal; Wang, Yaqi; Mao, Qi; Wu, Meijuan; Yan, Yaru; Ren, Jingjing; Wang, Xiaojuan; Liu, Airong; Chen, Shuangchen
Abstract: Bisphenol A (BPA) is an emerging organic pollutant, widely distributed in environment. Plants can uptake and metabolize BPA, but BPA accumulation induces phytotoxicity. In this study, we administered dopamine, a kind of catecholamines with strong antioxidative potential, to unveil its role in cucumber tolerance to BPA stress. The results showed that exposure to BPA (20 mg L −1 ) for 21 days significantly reduced growth and biomass accumulation in cucumber seedlings as revealed by decreased lengths and dry weights of shoots and roots. While BPA exposure decreased the chlorophyll content, cell viability and root activity, it remarkably increased reactive oxygen species (ROS) accumulation, electrolyte leakage and malondialdehyde (MDA) content, suggesting that BPA induced oxidative stress in cucumber. However, exogenous dopamine application significantly improved the photosynthetic pigment content, root cell viability, growth and biomass accumulation, and decreased the ROS and MDA levels by increasing the activity of antioxidant enzymes under BPA stress. Further analysis revealed that dopamine application significantly increased the glutathione content and the transcripts and activity of glutathione S -transferase under co-administration of dopamine and BPA compared with only BPA treatment. Moreover, dopamine decreased the BPA content in both leaves and roots, suggesting that dopamine promoted BPA metabolism by enhancing the glutathione-dependent detoxification. Our results show that dopamine has a positive role against BPA phytotoxicity and it may reduce the risks-associated with the dietary intake of BPA through consumption of vegetables. Graphical abstract: Image 1 Highlights: Bisphenol A (BPA) causes phytotoxicity in cucumber by inducing oxidative stress. Dopamine alleviates oxidative stress by improving antioxidant enzyme activity. Dopamine enhances glutathione content and glutathione S -transferase activity. Dopamine administration reduces BPA content in leaves and roots of cucumber. Dopamine promotes metabolism of BPA and may improve food safety.